2023
DOI: 10.3390/foods12193638
|View full text |Cite
|
Sign up to set email alerts
|

Marinades Based on Natural Ingredients as a Way to Improve the Quality and Shelf Life of Meat: A Review

Agnieszka Latoch,
Ewa Czarniecka-Skubina,
Małgorzata Moczkowska-Wyrwisz

Abstract: Marinating is a traditional method of improving the quality of meat, but it has been modified in response to consumer demand for “clean label” products. The aim of this review is to present scientific literature on the natural ingredients contained in marinades, the parameters of the marinating process, and certain mechanisms that bring about changes in meat. A review was carried out of publications from 2000 to 2023 available in Web of Science on the natural ingredients of meat marinades: fruit and vegetables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 260 publications
0
1
0
Order By: Relevance
“…Historically, the prevailing approach to water retention was the utilisation of inexpensive and efficient water retention chemicals containing phosphorus (Malik et al, 2023). Nevertheless, as consumer health consciousness continues to increase, there is a corresponding rise in the demand for natural and health-conscious food processing technologies (Latoch et al, 2023). Studies have revealed that enhancing feeding circumstances can contribute to an enhancement in the water retention capacity of fresh meat (Raghuvaran et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the prevailing approach to water retention was the utilisation of inexpensive and efficient water retention chemicals containing phosphorus (Malik et al, 2023). Nevertheless, as consumer health consciousness continues to increase, there is a corresponding rise in the demand for natural and health-conscious food processing technologies (Latoch et al, 2023). Studies have revealed that enhancing feeding circumstances can contribute to an enhancement in the water retention capacity of fresh meat (Raghuvaran et al, 2023).…”
Section: Introductionmentioning
confidence: 99%